If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(8 + -1a) = 18x(5 + -3a) (8 * 3x + -1a * 3x) = 18x(5 + -3a) Reorder the terms: (-3ax + 24x) = 18x(5 + -3a) (-3ax + 24x) = 18x(5 + -3a) -3ax + 24x = (5 * 18x + -3a * 18x) Reorder the terms: -3ax + 24x = (-54ax + 90x) -3ax + 24x = (-54ax + 90x) Solving -3ax + 24x = -54ax + 90x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '54ax' to each side of the equation. -3ax + 54ax + 24x = -54ax + 54ax + 90x Combine like terms: -3ax + 54ax = 51ax 51ax + 24x = -54ax + 54ax + 90x Combine like terms: -54ax + 54ax = 0 51ax + 24x = 0 + 90x 51ax + 24x = 90x Add '-24x' to each side of the equation. 51ax + 24x + -24x = 90x + -24x Combine like terms: 24x + -24x = 0 51ax + 0 = 90x + -24x 51ax = 90x + -24x Combine like terms: 90x + -24x = 66x 51ax = 66x Divide each side by '51x'. a = 1.294117647 Simplifying a = 1.294117647
| 5x+2y=-17 | | -6x-2y=24 | | 2x(a+c)= | | 3x^4-15x^3+6x^2-30x=0 | | 3x^4-15x^3+6x^2-30=0 | | 10d-15=12d | | x^4+2x^3+3x^2+18x-54=0 | | 3(x-7)+4(x+4)= | | -6y=24 | | -2(3-x)=30 | | .50y=1.5 | | 15a-2(4a+5)=-6a | | 3*12=.4y | | 10=5y-3y | | 6x-3x=12 | | -6(4-2x)=12x-24 | | 4x-3x=5 | | 2.5x+1.0x=7 | | 6x+33=5x | | 5m+3=18 | | -2n+3x=7 | | .50b+6=11 | | 8-x=12-2x | | b=9b-24 | | 9y^2-33y+24= | | -9+2(4g-7)=9 | | x+4=9-2x | | m+4+5=22 | | 33=x+4 | | z=1+i^12 | | 14+4=x+5x | | -160+-52x+1x^2+x^3=0 |